2020
DOI: 10.1088/1757-899x/998/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Expansive Soil by using Jute Fiber

Abstract: The instability of structure lies mainly in the properties of soil under which it is constructed. For instance, if the soil is having weak engineering properties, there are chances of crack formation and settlement. One of the major problematic soils of this type are the Black cotton soils which are mainly classified as expansive soils. They are obviously a hindrance to the strength and stability of structures. The present study deals with the improvement of soil characteristics with the addition of Jute fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In addition, the concentration in sample E increased over time. This increase in E has also been reported by several researchers who used different types of fibers, such as plastic fibers [16], sisal fibers [26], polypropylene fibers [12], and jute fibers [14].…”
Section: Compressive Strength Of Soil-fiber Mixturesupporting
confidence: 84%
“…In addition, the concentration in sample E increased over time. This increase in E has also been reported by several researchers who used different types of fibers, such as plastic fibers [16], sisal fibers [26], polypropylene fibers [12], and jute fibers [14].…”
Section: Compressive Strength Of Soil-fiber Mixturesupporting
confidence: 84%
“…Considering the Young's modulus [44], the addition of this fiber also resulted in an increase in sample consistency from very soft (i.e., E<4 MPa) to stiff in 1-7 days (i.e., 7<E<20 MPa) and to hard after 14 days (i.e., 20<E<32 MPa). Several researchers have also noticed this rise in the stiffness of fiber-reinforced soils [45][46][47][48]. The increase in strength and stiffness is only for samples with the addition of a 10 mm long fiber.…”
Section: Unconfined Compressive Strength Of Stabilized Claymentioning
confidence: 90%
“…The triaxial test and California Bearing Ratio (CBR) test were carried out on unstabilised and stabilised soil. According toLal et al (2020), the results of the California Bearing Ratio (CBR) test and the triaxial test show that the layered arrangement of the jute fibre reinforcement significantly improved the strength and stiffness properties of the soil. In addition, it can be concluded that placing two layers of jute fibre reinforcement is more effective than one or three layers Prasanna et al (2020).…”
mentioning
confidence: 99%